2020
DOI: 10.3389/fcimb.2019.00449
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenic Bacteroides fragilis: A Possible Etiological Candidate for Bacterially-Induced Colorectal Precancerous and Cancerous Lesions

Abstract: Enterotoxigenic Bacteroides fragilis (ETBF) produces Bacteroides fragilis toxin (BFT), which is associated with acute diarrheal, inflammatory bowel disease, and colorectal cancer (CRC). In experimental models, ETBF has been shown to contribute to colon carcinogenesis. The present study was conducted to investigate mucosal colonization of ETBF in the colon to find a possible association between the presence of ETBF and precancerous and cancerous lesions. The mucosal biopsies of involved sites were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 34 publications
3
88
1
Order By: Relevance
“…ETBF has been known as a contributor to chronic colonic diseases, including oncogenic transformation, intestinal in ammation, chronic colonic dysfunctions and colorectal precancerous and cancerous lesions (24)(25)(26)(27)(28). Combined action of the ETBF and IL-17 on colonic epithelial cells promoted the differentiation of monocytic-myeloid-derived suppressor cells(MO-MDSCs) and suppressed T-cell proliferation (27).…”
Section: Discussionmentioning
confidence: 99%
“…ETBF has been known as a contributor to chronic colonic diseases, including oncogenic transformation, intestinal in ammation, chronic colonic dysfunctions and colorectal precancerous and cancerous lesions (24)(25)(26)(27)(28). Combined action of the ETBF and IL-17 on colonic epithelial cells promoted the differentiation of monocytic-myeloid-derived suppressor cells(MO-MDSCs) and suppressed T-cell proliferation (27).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are recent data indicated that enterotoxigenic B. fragilis strains (ETBF) producing B. fragilis toxin (BFT) are associated with CRC, especially in the patients with precancerous lesions and initial carcinogenic lesions ( 40 ) and with ulcerative colitis, especially in the patients with diarrhea symptoms ( 41 ). Furthermore, some studies have been published recently, describing ETBF as a trigger for chronic Stat3/IL-17-driven colitis which is IL-17 dependent and induces T17 colitis and tumorogenesis through the secretion of the metalloproteinase Bft and other associated factors ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, enterotoxigenic Bacteroides fragilis and B . fragilis toxin gene was upregulated in patients with precancerous and cancerous lesions ( 67 ). Besides, microbial fermentation may have negative consequences owing to the generation of potentially toxic and cancer-promoting metabolites, such as ammonia, amines, phenols, sulphides, and nitrosamines ( 68 ).…”
Section: Microorganisms Inflammation and Cancermentioning
confidence: 99%